Two and a half million Syrian refugees, skill mix and capital intensity - Yusuf Emre Akgündüz; Huzeyfe Torun (Global Labor Organization (GLO), 2018)
We investigate how the rapid increase in the low-skilled labor supply induced by the inflow of 2.5 million Syrian refugees changed the tasks performed by native workers and the amount of capital used by firms in Turkey. Despite the unexpected nature of the refugee inflow, location choice of the refugees may be endogenous to the labor market opportunities of hosting regions. To handle this endogeneity issue, we use an instrument for the refugee intensity based on the distance of Turkish regions to the Syrian ones. The results based on Labor Force Survey suggest that the inflow of refugees increased natives' task complexity, reducing the intensity of manual tasks, and raising the intensity of abstract, routine and ICT tasks. This effect is particularly strong for natives with medium level of education. Exploiting the administrative firm data that contains the entirety of firms in the country, we find that the firms reduced their fixed assets. The fixed asset reduction is largest in machinery and equipment, which can be interpreted as a decline in the capital intensity of production. We conclude that tasks provided by Syrian refugees are substitutes for natives' manual tasks and firms' capital, and complementary to natives' more complex tasks.
Keywords: F22; J24; J21; D24; 330; Migration; refugees; labor-capital substitution; skills; tasks